ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA SMP KELAS VII DI KECAMATAN TONDANO BARAT - Manalu, Roito Brigita; Maukar, Marvel Grace; Regar, Vivian (Universitas PGRI Sumatera Barat, 2025)
Numeracy literacy is an important foundation in linking mathematical understanding with its application in everyday life. This ability includes mastery of basic mathematical operations, skills to interpret, analyse and solve contextual problems. The results of observations and interviews in a number of junior high schools in the West Tondano District area, students are generally fluent in reading but in counting, some other students still have difficulty. This study uses a quantitative descriptive approach with data collection through tests. The results showed that the categorisation of high, medium, and low groups had an average value for the high group of 66.33, the medium group of 22.96, and the low group of 9.33.